Equilibrium of micropolar bodies with predeformed regions. The superposition of large deformations. Issue 3 (2017) - Levin, V.A.
Abstract: A formulation of problems concerning the equilibrium of non-linearly elastic micropolar bodies is presented for the case of the superposition of large deformations. The kinematic relations of large deformation superposition theory are given for micropolar materials, and the constitutive relations and equilibrium equations of a micropolar medium in the intermediate state coordinates are obtained. Some results of the solution of a model problem based on large deformation superposition theory are presented.